Percepção do transplantado renal sobre a repercussão familiar ante seu adoecimento e tratamento - Borges, Daianne Cibele de Souza (Universidade Federal de São Carlos, 2015)
Kidney transplantation is an effective treatment recommended to chronic kidney disease. The discovery of the disease and the waiting for transplant affects hardly all the family. The research aims was to understand the impact of kidney transplantation in family life in the transplant recipient perspective, and understand how he realizes the importance of his family to the success of his transplant. This is a qualitative study using as theoretical and methodological framework Symbolic Interactionism and the Narrative, respectively. The identification of individuals was performed using a survey of the High Cost of Pharmacy county, since it is the location where they do drug withdrawal for treatment. The participants were 12 kidney transplant recipients who underwent transplantation in a period of up to 5 years who had primary caregiver a family member and who demonstrated clear thinking and consciousness. Data collection was made in a municipality in the state of São Paulo, through semi-structured interviews were audio recorded and were transcribed accurately. The analysis of the data emerged three themes: share the suffering: composed of 6 categories that depict the full impact that the family suffers from the illness until after transplantation; have a haven: represented by 5 categories that show all family effort to rebuild the face of adversity and fight for successful treatment and transplantation; and move on with the family: represented by four categories that describe the influence that the family has in the transplanted behavior throughout the experiment. Despite all the negative impact that the family suffers, it demonstrates is able to rebalance and provide the care and support needed for successful transplantation and coping with difficulties which affect the transplanted.
Keywords: Transplante renal; Família; Relacionamento familiar; Doença renal crônica; Enfermagem familiar; Kidney transplantation; Family relationship; Chronic kidney disease; Family nursing; Chronic disease; CIENCIAS DA SAUDE::ENFERMAGEM